Leading a TB team working with hard-to-reach clients. (24th February 2022) - Jarvis, Neil
Abstract : Neil Jarvis, Senior Charge Nurse and TB Lead Nurse, TB Team, The Royal Wolverhampton NHS Trust, (neiljarvis@nhs.net ) was runner-up in the Respiratory Nurse of the Year category of the BJN Awards 2021